2015
DOI: 10.1016/j.ijpsycho.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of response patterns in human auditory cortex during a target detection task: An intracranial electrophysiology study

Abstract: Selective attention enhances cortical activity representing an attended sound stream in human posterolateral superior temporal gyrus (PLST). It is unclear, however, what mechanisms are associated with a target detection task that necessitates sustained attention (vigilance) to a sound stream. We compared responses elicited by target and non-target sounds, and to sounds presented in a passive-listening paradigm. Subjects were neurosurgical patients undergoing invasive monitoring for medically refractory epileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
24
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 70 publications
13
24
2
Order By: Relevance
“…In the current study, classification performance was superior when features of the LFP were analyzed. In contrast, in an earlier report, high gamma activity within PLST, but not the AEP, was modulated strongly by attention and behavioral task (Nourski et al, 2014b; Steinschneider et al, 2014). …”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In the current study, classification performance was superior when features of the LFP were analyzed. In contrast, in an earlier report, high gamma activity within PLST, but not the AEP, was modulated strongly by attention and behavioral task (Nourski et al, 2014b; Steinschneider et al, 2014). …”
Section: Discussioncontrasting
confidence: 93%
“…For instance, this analysis has helped characterize the functional representation of phonetic categories used in speech (Pasley et al, 2011; Mesgarani et al, 2014) and the powerful effects of selective attention in modulating auditory cortical activity when listening to competing speech streams (e.g., Mesgarani and Chang, 2012). Analysis of high gamma activity has also demonstrated tiered effects of attention across auditory and auditory-related cortical areas (Nourski et al, 2014b; Steinschneider et al, 2014). All these findings parallel those obtained from patterns of spiking activity in experimental animals (e.g., Fritz et al, 2003; Mesgarani et al, 2008; Tsunada et al, 2011; Steinschneider et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Topographically, these results are consistent with the locus of modulations observed during auditory attention (33,40,49) and spatial discrimination tasks (47,60). Despite significant differences in experimental design and analysis, the results reported here defining regional sensitivity to sound location and auditory task processing are strikingly similar to those reported by Häk-kinen et al (43).…”
Section: Spatial Listening Effects On the Cortical Topography Of Binasupporting
confidence: 91%
“…Task-dependent modulation of AC activity has been demonstrated across a variety of experimental paradigms and methodological techniques, including animal electrophysiology (30)(31)(32), human electrocorticography (33,34), EEG/MEG (35)(36)(37)(38), monkey fMRI (39), and human fMRI (40)(41)(42)(43)(44)(45). The current study aimed to ascertain whether spatial listening alters the form of ITD and ILD sensitivity in human AC.…”
mentioning
confidence: 99%
“…Studies have demonstrated that early high gamma activity reflects more automatic processing that helps represent specific spectral characteristics of tone stimuli (Nourski et al, 2014a,b), as well as the remapping of acoustic speech characteristics to those representing phonetic categories (Chang et al, 2010; Travis et al, 2013; Mesgarani et al, 2014). In contrast, later high gamma activity on PLST could be strongly modulated by task requirements.…”
Section: Discussionmentioning
confidence: 99%